A systems level framework for postharvest physiology and quality preservation - García-Pastor, María E.; Falagán, Natalia (Frontiers, 2026)
The postharvest phase is critical for determining the quality, nutritional value, and market viability of fresh produce, yet global losses remain substantial, often exceeding 40%. This perspective aims to establish an integrated framework for understanding postharvest physiology and guiding sustainable quality preservation strategies. Deterioration is driven by complex molecular and physiological transformations, including ripening, senescence, and oxidative stress. Understanding these mechanisms is paramount for developing effective loss and waste reduction strategies. Metabolomics provides a systems level view of these changes, enabling the large scale profiling of small molecules and the identification of valuable biomarkers for quality loss, chilling injury, and senescence. Shifts in primary metabolites (sugars, organic acids) and the accumulation of ‘off aroma’ volatiles (ethanol, acetaldehyde) are critical indicators of decline. Also, preharvest factors (e.g. regulated deficit irrigation, signalling molecule application) fundamentally influence postharvest metabolic states by enhancing antioxidant capacity and delaying senescence. Molecular regulation, orchestrated by hormonal signalling (ethylene, abscisic acid) and transcription factors, underpins these shifts. Interventions focus on sustained redox homeostasis, often achieved through the exogenous application of ecofriendly signalling molecules like salicylic acid to upregulate enzymatic and non-enzymatic antioxidant systems. Integrating multi-omics technologies (metabolomics, transcriptomics) facilitates the identification of molecular targets for these interventions and supports predictive modelling for optimising storage conditions. Translating these integrated insights into sustainable, biomarker based, farm to fork strategies is essential for enhancing food security and mitigating global greenhouse gas emissions associated with food loss.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3008 Horticultural Production; Prevention; Generic health relevance; 2 Zero Hunger; 3004 Crop and pasture production; 3108 Plant biology